Cost-effectiveness of community health systems strengthening: quality improvement interventions at community level to realise maternal and child health gains in Kenya. Issue 3 (3rd March 2021) - Kumar, Meghan Bruce; Madan, Jason J; Auguste, Peter; Taegtmeyer, Miriam; Otiso, Lilian; Ochieng, Christian B; Muturi, Nelly; Mgamb, Elizabeth; Barasa, Edwine
Abstract : Introduction: Improvements in maternal and infant health outcomes are policy priorities in Kenya. Achieving these outcomes depends on early identification of pregnancy and quality of primary healthcare. Quality improvement interventions have been shown to contribute to increases in identification, referral and follow-up of pregnant women by community health workers. In this study, we evaluate the cost-effectiveness of using quality improvement at community level to reduce maternal and infant mortality in Kenya. Methods: We estimated the cost-effectiveness of quality improvement compared with standard of care treatment for antenatal and delivering mothers using a decision tree model and taking a health system perspective. We used both process (antenatal initiation in first trimester and skilled delivery) and health outcomes (maternal and infant deaths averted, as well as disability-adjusted life years (DALYs)) as our effectiveness measures and actual implementation costs, discounting costs only. We conducted deterministic and probabilistic sensitivity analyses. Results: We found that the community quality improvement intervention was more cost-effective compared with standard community healthcare, with incremental cost per DALY averted of 249 under the deterministic analysis and 76% likelihood of cost-effectiveness under the probabilistic sensitivity analysis using a standard threshold. The deterministic estimate of incremental cost per additional skilled delivery was US10, per additional early antenatal care presentation US155, per maternal death averted US5654 and per infant death averted US37 536 (2017 dollars). Conclusions: This analysis shows that the community quality improvement intervention was cost-effective compared with the standard community healthcare in Kenya due to improvements in antenatal care uptake and skilled delivery. It is likely that quality improvement interventions are a good investment and may also yield benefits in other health areas.